2018
DOI: 10.1186/s13023-018-0901-8
|View full text |Cite
|
Sign up to set email alerts
|

TSC-associated neuropsychiatric disorders (TAND): findings from the TOSCA natural history study

Abstract: BackgroundMost evidence for TSC-associated neuropsychiatric disorders (TAND) to date have come from small studies and case reports, and very little is known about TAND in adults. We explored baseline TAND data from the large-scale international TOSCA natural history study to compare childhood and adult patterns, describe age-based patterns, and explore genotype-TAND correlations.ResultsThe study enrolled 2216 eligible participants with TSC from 170 sites across 31 countries at the data cut-off for the third in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
124
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(147 citation statements)
references
References 38 publications
14
124
2
7
Order By: Relevance
“…We found that ADHD, social anxiety disorder, panic disorder and speci c phobia are the most common in this group. The incidence of ADHD in our cohort was signi cantly higher than that in the TOSCA cohort (51.58% vs. 22.4%) [21], and we suggest the following possible reasons: (1) The age distribution of children in the TOSCA cohort was 0-18 years old, while the age distribution of children in our cohort was 6-16 years old, which was consistent with the high incidence age of ADHD diagnosis. (2) Our cohort included TSC patients from all over the country.…”
Section: Discussionsupporting
confidence: 81%
“…We found that ADHD, social anxiety disorder, panic disorder and speci c phobia are the most common in this group. The incidence of ADHD in our cohort was signi cantly higher than that in the TOSCA cohort (51.58% vs. 22.4%) [21], and we suggest the following possible reasons: (1) The age distribution of children in the TOSCA cohort was 0-18 years old, while the age distribution of children in our cohort was 6-16 years old, which was consistent with the high incidence age of ADHD diagnosis. (2) Our cohort included TSC patients from all over the country.…”
Section: Discussionsupporting
confidence: 81%
“…They found that 88% of participants had at least one TAND manifestation endorsed and that 78% had four or more manifestations, but without identifying any specific TAND profile. Intellectual disability was present in 47% of the sample, similar to most findings in the literature . Difficulties in mathematics were most commonly observed (62%) out of all academic challenges and dual‐task deficits were most common (44%) of all neuropsychological deficits .…”
supporting
confidence: 82%
“…10,38 Finally, the surgery as a rare recourse in the therapy arsenal should be further investigated and a closer interaction with expert centers for epilepsy surgery should be encouraged. Our aim was to increase awareness on the disease and to present a picture of patients' characteristics and interventions in a very large number of centers dedicated for TSC care around the world.…”
mentioning
confidence: 99%
“…However, standardized neuropsychological and psychiatric assessment is still lacking in many countries, even in reference centers, and this should be better addressed and implemented. 10,38 Finally, the surgery as a rare recourse in the therapy arsenal should be further investigated and a closer interaction with expert centers for epilepsy surgery should be encouraged.…”
mentioning
confidence: 99%